Study protocol of the MUSED study: a randomized controlled trial to evaluate the psychobiological effects of group music therapy in women with depression - Gäbel, Christine; Rittner, Sabine; Stoffel, Martin; Jarczok, Marc N.; Aguilar-Raab, Corina; Ditzen, Beate; Warth, Marco (Nordisk tidsskrift for musikkterapi, 2021)
ABSTRACTIntroduction: People suﬀering from depression commonly show impaired emotionregulation, accompanied by deﬁcits in the regulation of psychobiological stresssystems. Initial studies indicate that music therapy can impact depressive symptomsand psychobiological mechanisms, and may therefore contribute to eﬀective treat-ment for depression.We will investigate the eﬀects of music therapy on depressive symptoms. Moreover,we will examine the impact of this therapy on circadian biological rhythms in daily life.In particular, we will monitor the circadian rhythm of vagal tone, indexed by heart ratevariability (HRV), and of the hypothalamic-pituitary-adrenal (HPA) axis, indexed by thediurnal cortisol proﬁle, within the framework of ecological momentary assessment(EMA).Method: Seventy-four women aged 18–65 years with a diagnosis of depression ordysthymia will be eligible for participation. Participants will be randomly assigned tothe intervention group (10 weeks music therapy + treatment as usual, TAU) or thecontrol group (TAU only).Self-report data will be collected before and after the intervention period, and10 weeks after the post-assessment. Psychobiological data (48 hours HRV, salivarycortisol from six samples each of two consecutive days) and observer ratings willbe gathered before and after the intervention period.Discussion: The study aims to validate previous ﬁndings that music therapy iseﬀective in the treatment of depression. The results will foster the understanding ofhow music therapy aﬀects HPA axis and autonomic regulation processes. The EMAapproach oﬀers the potential to test for covariance between diﬀerent psychobiologi-cal markers in daily life.